1988
DOI: 10.1177/153944928800800501
|View full text |Cite
|
Sign up to set email alerts
|

Value Acquisition in an Occupational Therapy Curriculum

Abstract: As the health care industry has become increasingly competitive, health care practitioners have become aware of the need to demonstrate that the occupational groups to which they belong perform unique and vital services to clients and patients. This awareness has fostered the development of a body of literature on professional identity and development that includes discussion of the role of values in defining and differentiating professional groups The purpose of this study was to begin exploration and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…They also discovered that their role-playing behaviours were often inconsistent with the principles of client involvement and choice that is inherent to psychiatric rehabilitation and also to the pro fessional values of the profession. This inconsistency is similar to the findings of DePoy and Merrill (1982) who studied the acquisition of professional val ues by occupational therapy students. They observed that students could articulate the values but observations of their practice and learning activities in the classroom revealed behaviours that were often at odds with the stated values.…”
Section: The Course Designcontrasting
confidence: 34%
“…They also discovered that their role-playing behaviours were often inconsistent with the principles of client involvement and choice that is inherent to psychiatric rehabilitation and also to the pro fessional values of the profession. This inconsistency is similar to the findings of DePoy and Merrill (1982) who studied the acquisition of professional val ues by occupational therapy students. They observed that students could articulate the values but observations of their practice and learning activities in the classroom revealed behaviours that were often at odds with the stated values.…”
Section: The Course Designcontrasting
confidence: 34%
“…However, the notions of client-centred practice, which were articulated by Yerxa (1983) and refined and codified by Law et al (1995), were also apparent throughout the interviews and especially with the third year students. DePoy and Merrill (1988) found that their students could articulate the values of occupational therapy but could not put them into practice. The results of this research would appear to be the reverse of this.…”
Section: Discussionmentioning
confidence: 97%
“…(Participant 4,year 3. ) DePoy and Merrill (1988) found that students could articulate the values of occupational therapy, but were not always clear about its usefulness. The same may be said of the students in this study.…”
Section: What Is Empowerment?mentioning
confidence: 98%
See 1 more Smart Citation
“…While some type of similarity between occupational therapy faculty and students is likely, available evidence about allied health faculty and students indicates that clear variations in styles and even values exist (DePoy & Merrill, 1988;Ditiberio & Hammer, 1993;Freeman & Tijerina, 2000;Joyce-Nagata, 1996;Linares, 1999;Myers & McCaulley, 1985).…”
Section: Implications For Teaching Strategiesmentioning
confidence: 99%